Differences of Mothers Knowledge in The First Treatment of Febrile Seizures for Children Under Five Before and After Being Educated with Leaflet Media at Sakura Ward - Putu Nevi Erliawati; Ni Wayan Suarniti; Ni Wayan Armini (Universitas Muhammadiyah Semarang, 2025)
Introduction: Febrile seizures are convulsions in children triggered by a body temperature above 38°C without intracranial abnormalities. This condition may cause delayed brain development, paralysis, mental retardation, and 2–10% may progress to epilepsy or death. Methods: This study aimed to determine the difference in mothers’ knowledge about first aid for febrile seizures in children under five before and after health education using leaflet media. The research was conducted from September to October 2024 in the Sakura Ward of Buleleng Regency Hospital with 32 respondents selected through purposive sampling. A pre-experimental one-group pretest–posttest design was applied. Results: Before the intervention, 90.6% of respondents had low knowledge, while after the intervention, 93.8% had good knowledge. The paired t-test obtained a p-value of 0.000 (<0.05), indicating a significant difference in mothers’ knowledge before and after education. Conclusion: Health education using leaflet media effectively improves mothers’ knowledge about first aid for febrile seizures in toddlers. Health workers are advised to use leaflet media as a concise, clear, and efficient educational tool for febrile seizure prevention.